BuySmarter - Lori Ruderman; Kenneth Thomson (Blockchain in Healthcare Today, 2018)
Session Description: BUYSMARTER is a transformative, data-driven initiative leveraging the collective purchasing power ($24B/year) of the U.S. Department of Health and Human Services (HHS) to secure lower prices, achieve operational efficiencies, and generate cost savings on goods and services.